2017
DOI: 10.1182/blood-2017-05-783225
|View full text |Cite
|
Sign up to set email alerts
|

Clonal evolution and outcomes in myelofibrosis after ruxolitinib discontinuation

Abstract: Despite significant improvements in the signs and symptoms of myelofibrosis (MF), and possible prolongation of patients' survival, some have disease that is refractory to ruxolitinib and many lose their response over time. Furthermore, patients with ≥3 mutations are less likely to respond to ruxolitinib. Here we describe outcomes after ruxolitinib discontinuation in MF patients enrolled in a phase 1/2 study at our center. After a median follow-up of 79 months, 86 patients had discontinued ruxolitinib (30 of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
171
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(187 citation statements)
references
References 16 publications
(18 reference statements)
12
171
0
4
Order By: Relevance
“…Outcomes were particularly poor in patients who had molecular clonal evolution and thrombocytopenia. 13 A second study of 64 patients treated in a real-life comparison confirmed that responses to salvage treatments are rare. 14 Understanding that the outcome after ruxolitinib is important for identifying patients who may benefit from specific interventions, such as allogeneic stem cell transplantation, 15 second-generation JAK inhibitors, [16][17][18] drugs with alternative mechanisms of action, 19,20 or investigational agents in combination with ruxolitinib.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Outcomes were particularly poor in patients who had molecular clonal evolution and thrombocytopenia. 13 A second study of 64 patients treated in a real-life comparison confirmed that responses to salvage treatments are rare. 14 Understanding that the outcome after ruxolitinib is important for identifying patients who may benefit from specific interventions, such as allogeneic stem cell transplantation, 15 second-generation JAK inhibitors, [16][17][18] drugs with alternative mechanisms of action, 19,20 or investigational agents in combination with ruxolitinib.…”
Section: Introductionmentioning
confidence: 85%
“…The outcome of patients who failed ruxolitinib within the phase 1/2 trial reportedly was poor (median survival, 14 months). Outcomes were particularly poor in patients who had molecular clonal evolution and thrombocytopenia . A second study of 64 patients treated in a real‐life comparison confirmed that responses to salvage treatments are rare .…”
Section: Introductionmentioning
confidence: 88%
“…6 Furthermore, ruxolitinib discontinuation is associated with a short survival of approximately 14 months. [9][10][11] At present allogeneic stem cell transplantation (ASCT) is the only potentially curative therapy. 12,13 However, morbidity and mortality are high from conditioning regimen toxicity, acute and chronic graft vs host disease (GVHD), infection and relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term observations indicate that ruxolitinib needs to be stopped in 55% of patients after three-year follow-up (data from COMFORT-I and -II trials) [46]. Median OS after stopping ruxolitinib is 14 months [47].…”
Section: How To Withdraw Ruxolitinib? Principles Of Ending Therapymentioning
confidence: 99%